Stereoselective Substrate‐Controlled Asymmetric Syntheses of both 2, 5‐cis‐ and 2, 5‐trans‐Tetrahydrofuranoid Oxylipids: Stereodivergent Intramolecular Amide Enolate Alkylation. Issue 22 (21st April 2016) - Jang, Hongjun; Shin, Iljin; Lee, Dongjoo; Kim, Hyoungsu; Kim, Deukjoon
Abstract: The concise, highly stereoselective, substrate‐controlled asymmetric total syntheses of both 2, 5‐cis‐ and 2, 5‐trans‐tetrahydrofuranoid nematocidal oxylipids from the Australian brown algae Notheia anomala have been accomplished in a stereodivergent fashion. The highly stereoselective intramolecular amide enolate alkylation strategy provides access to both stereoisomers of the 3‐hydroxy‐2, 5‐disubstituted tetrahydrofuran core of these marine natural products through chelate and nonchelate control, which is driven by the C3‐hydroxy protecting group. This approach offers an optional and highly stereoelective access to any of the eight possible stereoisomers of the 2, 5‐disubstituted‐3‐oxygenated tetrahydrofuran skeleton, an important structural feature which is present in many biologically active natural products. Abstract : Two from one : The title reaction leads to both isomers of the tetrahydrofuranoid nematocidal oxylipids in a stereodivergent fashion from a common intermediate. Each of the stereoisomers results from exploiting either chelate or nonchelate control in the reaction. PMB= para ‐methoxybenzyl, TIPS=triisopropylsilyl.